Trace of doubt [large type] - Mills, DiAnn (Center Point Large Print, 2022)
"Fifteen years ago, Shelby Pearce confessed to murdering her brother-in-law and was sent to prison. Now she's out on parole and looking for a fresh start in the small town of Valleysburg, Texas. But starting over won't be easy for an ex-con. FBI Special Agent Denton McClure was a rookie fresh out of Quantico when he was first assigned the Pearce case. He's always believed Shelby embezzled five hundred thousand dollars from her brother-in-law's account. So he's going undercover to befriend Shelby, track down the missing money, and finally crack this case. But as Denton gets closer to Shelby, he begins to have a trace of doubt about her guilt. Someone has Shelby in their crosshairs. It's up to Denton to stop them before they silence Shelby - and the truth - forever"--